2007
DOI: 10.1182/blood-2006-12-062851
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase reverse-transcriptase homozygous mutations in autosomal recessive dyskeratosis congenita and Hoyeraal-Hreidarsson syndrome

Abstract: Dyskeratosis congenita (DC) is a multisystem bone marrow failure syndrome characterized by a triad of mucocutaneous abnormalities and an increased predisposition to malignancy. X-linked DC is due to mutations in DKC1, while heterozygous mutations in TERC (telomerase RNA component) and TERT (telomerase reverse transcriptase) have been found in autosomal dominant DC. Many patients with DC remain uncharacterized, particularly families displaying autosomal recessive (AR) inheritance. We have now identified novel h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 56 publications
2
120
0
4
Order By: Relevance
“…54 Also of note, mutations in the TERT gene have been identified in some patients with aplastic anemia and short telomeres. 55 Further confusing the picture is a hypomorphic Dkc1 mutant mouse, which demonstrated impaired ribosomal RNA pseudo-uridylation before the onset of clinical features of DKC, whereas reductions in telomere length became evident only in later generations.…”
Section: Dyskeratosis Congenitamentioning
confidence: 99%
“…54 Also of note, mutations in the TERT gene have been identified in some patients with aplastic anemia and short telomeres. 55 Further confusing the picture is a hypomorphic Dkc1 mutant mouse, which demonstrated impaired ribosomal RNA pseudo-uridylation before the onset of clinical features of DKC, whereas reductions in telomere length became evident only in later generations.…”
Section: Dyskeratosis Congenitamentioning
confidence: 99%
“…Observations that HHS is more frequent in boys and presents with progressive bone marrow failure, led to the speculation that HHS may be a variant of DC. Subsequent molecular analyses confirmed that individuals diagnosed with HHS showed mutations in DKC1 and TERT [181][182][183][184]. Patients were also found to have shortened 3′ telomeric overhangs [185].…”
Section: Hoyeraal-hreidarsson Syndromementioning
confidence: 63%
“…Only selective intronic and regulatory region SNPs are listed due to space limitation, but the full list can be found at the dbSNP website. As well, rare disease-associating mutations are not listed here, but are summarized in several review articles [166,183]. At the time of writing this review, TIN2 is the only member of the shelterin complex identified with disease-associating genetic variations.…”
Section: Gar1mentioning
confidence: 99%
“…(Heiss, Knight et al 1998;Vulliamy, Marrone et al 2001;Vulliamy, Walne et al 2005;Marrone, Walne et al 2007;Walne, Vulliamy et al 2007;Savage, Giri et al 2008;Vulliamy, Beswick et al 2008) All are components of the telomerase complex or shelterin (Fig 4). The X-linked recessive disease is a common form of DC.…”
Section: Dyskeratosis Congenita Genesmentioning
confidence: 99%